Drawing helps children to talk about their presenting problems during a mental health assessment. (January 2015) - Woolford, Junie; Patterson, Tess; Macleod, Emily; Hobbs, Linda; Hayne, Harlene
When children require mental health services, clinicians need to conduct assessments that are developmentally sensitive and that include the child's point of view. Drawing is a popular tool that is commonly used in clinical settings. Research on drawing in experimental settings has confirmed that the opportunity to draw while talking increases the amount of verbal information that children report during an interview. The present research examined whether drawing also facilitates children's self reports during a mental health assessment. A total of 33 5–12-year-old children were asked either to draw and tell about their presenting problem or to tell only. Children who drew and told provided twice as much verbal information as children who told only. Further, interviewers in the draw and tell condition used a greater number of minimal responses than did interviewers in the tell only condition. These data have important implications for clinical practice.